Non-destructive Plant Morphometric and Color Analyses Using an Optoelectronic 3D Color Microscope - Lazcano-Ramírez, Hugo G.; Gómez-Felipe, Andrea; Díaz-Ramírez, David; Durán-Medina, Yolanda; Sánchez-Segura, Lino; de Folter, Stefan; Marsch-Martínez, Nayelli (Frontiers in Plant Science, 2018)
Gene function discovery in plants, as other plant science quests, is aided by tools that image, document and measure plant phenotypes. Tools that acquire images of plant organs and tissues at the microscopic level have evolved from qualitative documentation tools, to advanced tools where software-assisted analysis of images extracts quantitative information that allows statistical analyses. They are useful to perform morphometric studies that describe plant physical characteristics and quantify phenotypes, aiding gene function discovery. In parallel, non-destructive, versatile, robust, and user-friendly technologies have also been developed for surface topography analysis and quality control in the industrial manufacture sector, such as optoelectronic 3D color microscopes. These microscopes combine optical lenses, electronic image sensors, motorized stages, graphics engines and user-friendly software to allow the visualization and inspection of objects of diverse sizes and shapes from different angles. This allow the integration of different automatically obtained images along the Z axis of an object, into a single image with a large depth-of-field, or a 3D model in color. In this work we explored the performance of an optoelectronic microscope to study plant morphological phenotypes and plant surfaces in different model species. Furthermore, as a “proof-of-concept”, we included the phenotypic characterization (morphometric analyses at the organ level, color, and cell size measurements) of Arabidopsis mutant leaves. We found that the microscope tested is a suitable, practical and fast tool to routinely and precisely analyze different plant organs and tissues, producing both high-quality, sharp color images and morphometric and color data in real time. It is fully compatible with live plant tissues (no sample preparation is required) and does not require special conditions, high maintenance, nor complex training. Therefore, though barely reported in plant scientific studies, optoelectronic microscopes should emerge as convenient and useful tools for phenotypic characterization in plant sciences.